Milling of Nanoparticles Reinforced Al-Based Metal Matrix Composites - Pramanik, Alokesh; Basak, A.; Dong, Yu; Shankar, S.; Littlefair, G. (MDPI AG, 2018)
This study investigated the face milling of nanoparticles reinforced Al-based metal matrix composites (nano-MMCs) using a single insert milling tool. The effects of feed and speed on machined surfaces in terms of surface roughness, surface profile, surface appearance, chip surface, chip ratio, machining forces, and force signals were analyzed. It was found that surface roughness of machined surfaces increased with the increase of feed up to the speed of 60 mm/min. However, at the higher speed (100–140 mm/min), the variation of surface roughness was minor with the increase of feed. The machined surfaces contained the marks of cutting tools, lobes of material flow in layers, pits and craters. The chip ratio increased with the increase of feed at all speeds. The top chip surfaces were full of wrinkles in all cases, though the bottom surfaces carried the evidence of friction, adhesion, and deformed material layers. The effect of feed on machining forces was evident at all speeds. The machining speed was found not to affect machining forces noticeably at a lower feed, but those decreased with the increase of speed for the high feed scenario.